English– and Arabic-Medium of Instruction and Second Language Acquisition of English Articles System by ESL Arab Sophomores in Sharjah - Shalaby, Atia Ibrahim Atia (2014)
This study investigates the acquisition of the English articles system by Arab sophomores in Sharjah in the UAE, one group being taught through the medium of English and the other through the medium of Arabic. The main focus of the study is the extent to which the medium of instruction affects the acquisition of the articles system. The role of mother tongue transfer in this process is also examined. Initially a quick placement test was applied to exclude low-achievers, and then two instruments were adopted. The first instrument is an English article forced-elicitation task which comprises thirty contexts; eighteen of them are adopted from Ionin, Ko and Wexler (2004), but with some modifications, the other twelve are generated by the researcher to meet the objectives of this study. The participants completed this task within a fifty-minute class period. The second instrument is a written argumentative essay, in which the participants are asked to choose one of three assigned topics and to produce a 250-word essay in their own time away classroom constraints. The samples of the study are 158 male Arab sophomores; 104 are from Arab medium of instruction whereas the rest 54 are from English medium of instruction high schools. The findings reveal that the EMI group significantly (p<0.005) outperforms their peers in the AMI environment in the acquisition of the EAS. The findings are interpreted in the light of the participants’ L1 Arabic influences. The pedagogical implications of the study are discussed in the final part of the dissertation and recommendations are made for further studies.